Well said intro: pronunciation for clear communication - Linda Grant; Eve Einselen Yu (Boston, Massachusetts : National Geographic Learning, 2017)
"Designed to improve the pronunciation and communication skills of students from all language backgrounds, from beginning to low intermediate levels."
Keywords: English language Sound recordings for foreign speakers; English language Conversation and phrase